2015
DOI: 10.2146/ajhp140621
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing inhalers to patients with chronic obstructive pulmonary disease on hospital discharge: Effects on prescription filling and readmission

Abstract: A targeted pharmacy program to provide COPD patients being discharged from the hospital with the multidose inhalers they had used during hospitalization was associated with improved medication adherence, as measured by prescription filling behavior, and reduced rates of 30- and 60-day hospital readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
0
26
0
2
Order By: Relevance
“…Ensuring that patients have all required outpatient respiratory medications in-hand before discharge is an intervention that could improve readmissions. Blee et al 69 reported a reduction in 30-day all-cause readmissions from 21.4% to 8.7% after having pharmacists dispense outpatient respiratory inhalers and deliver inhaler instructions to patients prior to discharge. Because this study used a pre-post intervention analysis, confounding due to different policies implemented at the same time could be present, but removing the additional step for patients to obtain medications after discharge seems likely to be beneficial.…”
Section: Predicting Patients Once Identified At High Risk For Aecopmentioning
confidence: 99%
“…Ensuring that patients have all required outpatient respiratory medications in-hand before discharge is an intervention that could improve readmissions. Blee et al 69 reported a reduction in 30-day all-cause readmissions from 21.4% to 8.7% after having pharmacists dispense outpatient respiratory inhalers and deliver inhaler instructions to patients prior to discharge. Because this study used a pre-post intervention analysis, confounding due to different policies implemented at the same time could be present, but removing the additional step for patients to obtain medications after discharge seems likely to be beneficial.…”
Section: Predicting Patients Once Identified At High Risk For Aecopmentioning
confidence: 99%
“…Additionally, case management successfully assisted patients through financial aid and pharmaceutical discount programmes that were not compliant with the prescribed medication regimen due to medication availability issues and patient financial constraints. Other studies have noted similar issues with non‐adherence to medication regimens that contribute to patient readmissions (Blee, Roux, Gautreaux, Sherer, & Garey, ). Plus, medication profile errors were rectified during telephonic communication in the patient's electronic medical record.…”
Section: Discussionmentioning
confidence: 69%
“…Other studies have noted similar issues with non-adherence to medication regimens that contribute to patient readmissions (Blee, Roux, Gautreaux, Sherer, & Garey, 2015). Plus, medication profile errors were rectified during telephonic communication in the patient's electronic medical record.…”
Section: Discussionmentioning
confidence: 94%
“…20 Each bundle component is evidence-based, applicable to all COPD patients, and was deemed highyield for local context. The bundle components were designed to provide an appropriate COPD medication regimen, 22 a 30-d medication supply of insurance-compatible inhalers, 23 personalized inhaler education, 24 standardized discharge instructions, 24 and a primary care follow-up appointment scheduled within 15 d.…”
Section: Copd Care Bundlementioning
confidence: 99%